Education Process Using Learning Videos for Students in SD Katolik 15 St. Laurentius Manado - Lianly Rompis; Julie Rante; Ryan Singgeta; Alexander Patras; Kristian Dame; Verna Bokau; Chrysantus Padachan; Victori Polly (Journal of Innovation and Community Engagement, 2021)
This community service activity is a form of dedication from Lecturers of Electrical Engineering Study Program in Universitas Katolik De La Salle Manado to apply the sciences and skills in helping Indonesia that currently is facing a global problem which is related to the appearance of Covid-19 virus. It is of course gives impact in education system that indirectly forcing people to do an online learning and all the lecturers have to work from home. This matter encouraged us as lecturers in Electrical Engineering Study Program Universitas Katolik De La Salle Manado to help maintaining the education process of students in SD Katolik 15 St. Laurentius Manado so they can study well and gain knowledge from home through online learning. What we actually did was together with our Electrical Engineering students created a simple learning material in the form of video. The main topic for our material is related to electricity. As a result, we designed and created three learning videos for the students and we hope that these will help the students to briefly understand the basic concept of electricity and how to make a simple electric circuit. We are also hoping that this activity will help the parents economically to support the education of their children. The outcome of this community service activity are videos and report. Keywords: community service; electricity; elementary school; learning video